The method of limitation of dynamic loads of nonlinear electromechanical systems under state vector robust control - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Voloshko, O. V.; Kolomiets, V. V.; Kobilyanskiy, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Development of the method of limitation of dynamic loads of nonlinear electromechanical systems under state vector robust control. MethodologyLimitation of dynamic loads of nonlinear electromechanical systems is carried out using the minimum selector of choosing the minimum value of the control vector from formed with the help of local controllers and with the vector of maximum control values. Calculation of the gain coefficients of nonlinear robust controllers and observers are based on solutions of the Hamilton–Jacob–Isaacs equations. Results. The results of computer simulation of transitional processes of main roll drives of the rolling mill 950 of the Zaporozhye plant «Dnіprospetsstal» with limitation of dynamic loads are given. Originality. For the first time the method of limitation of dynamic loads of nonlinear electromechanical systems under state vector robust control based on minimum selector and nonlinear robust control of state variables which is needed limitation is developed. Practical value. Examples of transitional processes of main roll drives of the rolling mill 950 of the Zaporozhye plant «Dnіprospetsstal» with limitation of dynamic loads are given.

Розробка методу обмеження динамічних навантажень нелінійних електромеханічних систем при векторному робастному управлінні. Методологія. Обмеження динамічних навантажень нелінійних електромеханічних систем здійснюється за допомогою селектора вибору мінімального значення вектора керування із сформованого за допомогою локальних регуляторів та вектора максимальних значень керування. Розрахунок коефіцієнтів підсилення нелінійних робастних контролерів і спостерігачів базується на рішеннях рівнянь Гамільтона–Якобі–Айзека. Результати. Наведено результати комп’ютерного моделювання перехідних процесів головних приводів валків прокатного стану 950 Запорізького заводу «Дніпроспецсталь» із обмеженням динамічних навантажень. Оригінальність. Вперше розроблено метод обмеження динамічних навантажень нелінійних електромеханічних систем при робастному управлінні за вектором стану на основі селектору мінімуму та нелінійних робастних регуляторів змінних стану, які необхідно обмежуват. Практична цінність. Наведено приклади перехідних процесів головних приводів прокатного стану 950 Запорізького заводу «Дніпроспецсталь» із обмеженням динамічних навантажень.
Keywords: nonlinear electromechanical systems; state vector robust control; Hamilton–Jacobi–Isaacs equations; limitation of dynamic loads; computer simulation; нелінійні електромеханічні системи; робастне керування за вектором стану; рівняння Гамільтона– Якобі–Айзека; обмеження динамічних навантажень; комп’ютерне моделювання